ETHICAL LEADERSHIP FOR INTERNAL AUDITOR: AN EXAMINATION OF SOCIAL COGNITIVE THEORY - Anggraini, Francisca Reni Retno; Siswanto, Fransiscus Asisi Joko (UI Scholars Hub, 2019)
This study aims to empirically examine the influence of subjective norms, behavioral control, and intention on the attitude of internal auditors to report fraud with ethical leadership as a moderating variable. This study used a scenario-based survey of internal auditors working in state-owned and mid-level private companies. The sample was chosen by the non-random method because the sample was taken from the participants of the SNIA (National Internal Auditor Symposium) and in total, 117 respondents were gathered as valid samples. Data were analyzed using Warp PLS 4.0. This study proves that subjective norms and behavioral control have a positive effect on the attitude of internal auditors to report fraud, while intention has a negative influence on the attitude. Ethical leadership strengthens the positive influence of subjective norms and behavioral control on the attitude of the internal auditors. It also reinforces the negative influence of intention on the internal auditors’ attitude. This research supports a model of integration between Theory of Planned Behavior and Social Cognitive Theory, which states that the environment, in this case ethical leadership, influences the internal auditor's cognition in making ethical decisions. However, this study cannot prove that ethical leadership can reduce the negative influence of intention on the attitude of internal auditors to report fraud.